Rural Community Teachers’ Awareness and Attitude on Learning Challenges - Rajkumari S; Ramya Bhaskar (Journal of Extension Education, 2024)
In rural landscapes, teachers are unsung education heroes, facing challenges like limited professional growth, inadequate infrastructure, and the need to innovate teaching methods for diverse student needs. They shape their communities’ education through adaptability and evolution. A September 2022 study conducted in Coimbatore district of Tamil Nadu surveyed 149 rural primary school teachers, using self-developed questionnaires on background information, awareness of learning challenges, and attitudes toward them. Reliability, measured with Cronbach’s Alpha, showed scores of 0.829 for awareness and 0.854 for attitudes. Results revealed that most teachers had moderate awareness, with some displaying low awareness and many holding neutral attitudes, which could turn unfavorable over time. Linear regression highlighted associations with age, experience, and class type. Experience emerged as the main predictor for both awareness and attitude, implying that more experience leads to improved awareness and attitude. These findings can guide stakeholders in supporting rural educators, benefitting students across geographical boundaries.